Pastel painting step-by-step - Coombs, Peter, -2007; Evans, Margaret, 1952-; Hardy, Paul E., 1924- (Step by step (Tunbridge Wells, England)., 2020)
A comprehensive guide to painting with pastels including easy instructions on how to master tone, colour blending, composition, perspective, and more.